Masterworks of 20th century music the modern repertory of the symphony orchestra - Lee, Douglas A. 1932- (Routledge, 2002)
"Introduces more than one hundred of the most popular and frequently performed classical works of our era; includes works by Copland, Ives, Gershwin, Bartok, Stravinsky, Prokofiev, Ravel, Shostakovich, and many more"--P. [4] of cover.
Keywords: Geschichte 1900-2000; Orchestre, Musique d' - 20e siècle - Analyse et appréciation; Orchestral music -- 20th century -- Analysis, appreciation; Orchestermusik; Führer